Effect of GeI2 and GeBr2 incorporation on perovskite properties and performance of carbon-based perovskite solar cells - Aunping, Namfon; Kumlangwan, Pantiwa; Towannang, Madsakorn; Chanlek, Narong; Kumnorkaew, Pisist; Klangtakai, Pawinee; Srepusharawoot, Pornjuk; Thongnum, Anusit; Chompoosor, Apiwat; Jarernboon, Wirat; Pimanpang, Samuk; Ruttanapun, Chesta; et al. (My University, 2023)
CH3NH3PbI3 (MAPbI3) film was prepared by a convective method, and its X-ray diffraction spectrum displays the tetragonal perovskite structure. GeI2 and GeBr2 powders dissolve poorly in a mixed dimethylformamide-dimethylsulfoxide (DMF-DMSO) solvent, but the introduction of 5 wt% 5-ammonium valeric acid iodide (5-AVAI) into the mixed DMF-DMSO solvent greatly promotes GeI2 and GeBr2 solubility. XRD spectra of the (5-AVAI)MAPbI3, MAGexPb1–xI3, and MAGexPb1–xBr2xI3–2x (x = 0.0625 and 0.125) films exhibit a tetragonal perovskite structure, but the film morphologies become rougher than that of the pristine MAPbI3 film. Discontinuous islands are formed on MAGexPb1–xI3 and MAGexPb1–xBr2xI3–2x (x = 0.125) films. X-ray photoemission spectroscopy (XPS) analysis detected the Ge element on all Ge-doped films. The best performance levels of the carbon-based hole transport layer-free MAGexPb1–xI3–x (x = 0.0625, η= 3.63%) and MAGexPb1–xBr2xI3–2x (x = 0.0625, η = 2.95%) perovskite solar cells are lower than that of the pristine MAPbI3–based perovskite solar cell (η = 5.28%). This is likely due to the increased surface roughness, pin-holes, isolated islands, and the decreased light absorbance of the Ge-doped films in comparison with the pristine MAPbI3 film.
Keywords: 5-AVAI; Carbon; Ge-Pb perovskite; Perovskite solar cell